Konsep Keberbakatan, Anak Berbkat dan Pendidikannya - Habsy, Bakhrudin All; Febrianti, Aliya Putri; Sari, Wahyu Asri Nur Tri Via; Azizah, Elsa Nur (TSAQOFAH, 2024)
The talents that each individual has are different. Each individual has his own abilities and potential. Talent is a natural ability of a person that needs to be trained and developed. The importance of developing talents so that the potential they have can be realized to the maximum. Talent development requires a platform, especially in education. Education greatly affects the potential of the individual. The need for an educational program as an effort to develop children with special talents. The talent development program should correspond to the talents possessed and also take into account the characteristics of the child. Therefore, the purpose of this study is to identify the giftedness of the child and his education. This research uses qualitative methods with a literature study or library study approach.